Consistent Estimation of Cross-Sectional Models in Event Studies - Eckbo, B. Espen; Maksimovic, Vojislav; Williams, Joseph (Review of Financial Studies, 1990)
Event studies often include cross-sectional regressions of announcement effects on exogenous variables. If the event is voluntary and investors are rational, then standard OLS and GLS estimators are inconsistent. Consistent ML estimators are constructed for a cross-sectional model of horizontal mergers relating announcement effects to exogenous characteristics of firms and industries. The OLS and ML estimates differ dramatically for bidders but not for targets. The evidence suggests that managers of bidders, but not targets, have valuable private information about the potential synergies from proposed mergers.